Novel technique of fixing intracorneal rings segments after migration - Agarwal, Prateek (BMJ Case Rep, 2020)
A 38-year-old patient with a history of non-progressive keratoconus in the left eye presented to us with an uncorrected visual acuity of 20/400, which improved to 20/60 with pinhole. We planned for intracorneal rings segment in the left eye. Postoperatively uncorrected visual acuity improved to 20/30. The patient presented 2 weeks later with severely decreased vision to 20/100 and migration of intracorneal rings were noted with both the rings riding side by side. The patient gave history of vigorous eye rubbing. The rings were repositioned with the help of Sinskey hooks and superior ring was anchored with 10-nylon suture passed through the ring hole to the corneal stroma. Two more sutures were placed radial to the circumference of inferior ring to prevent its migration. The sutures were removed after 1 month and the patient was followed up with stable position of the rings for the next 6 months. The uncorrected visual acuity improved to 20/40.